Between practices and demands: ambiguities, controversies and constraints in the emergence of active citizenship in Turkey - Bee, Cristiano; Kaya, Ayhan (Routledge Journals, Taylor & Francis Ltd, 2017)
This article discusses the emergence of active citizenship in Turkey in the light of two working definitions that provide different outcomes in terms of research objectives and aims. On the one side, we define active citizenship as a practice stimulated by public institutions through public policy with the aim of promoting civic and political engagement in order to shape participatory policy processes and ultimately improve the democratic bases of policy-making. On the other side, we define active citizenship as a demand, which becomes particularly important where the civil society expresses certain claims through different means using both traditional and alternative channels of mobilization. In our discussion, we have examined different macro-processes and macro-events that have been key in bringing about different formulations of active citizenship. Using a case study method - where we overview different contextual elements/dynamics that bring to the fore various elements of civic and political engagement and civic and political participation during the past 15years - we argue that, in a context where the expression of active citizenship is volatile and constrained, further research should take into account different top-down and bottom-up dynamics that bring about different challenges for the study of this subject in Turkey.
Keywords: Active Citizenship; Civil Society; Civic Engagement; Civic Participation; Political Engagement; Political Participation; Turkey; Europeanization; Occupygezi; Citizenship; Civil-Society; Gezi Park; Participation; Earthquake; Policy; Engagement; State